Kirurško zdravljenje prostatične obstrukcije pri bolnikih s simptomi spodnjih sečil - Jagodič, Klemen (Farmacevtski vestnik, 2014)
Low urinary track symptoms (LUTS) are an increasing quality of life issue for many men in the age. In spite of many different causes, benign prostatic obstruction (BPO) due to benign prostatic enlargement (BPE) is the most common cause of LUTS. BPE is a chronic, slowly progressive disease. Prostate surgery is usually required when patients have experienced recurrent or refractory urinary retention, overflow incontinence, recurrent urinary tract infections, bladder stones or diverticula, treatment-resistant macroscopic haematuria or dilatation of the upper urinary tract with or without renal insufficiency (absolute operation indications, need for surgery. Surgery is usually needed after medicament treatments failure (relative operation indications) . For 8 decades, transurethral resection of the prostate has been considered the cornerstone of surgical management for BPO. Small prostate are suitable for transurethral incision of the prostate. Open prostatectomy is the oldest surgical treatment modality. It is a choice of treatment for prostates >80ccm. Despite modern medicament treatment, surgery still plays an important role in the treatment of LUTS/BPO.
Keywords: kirurško zdravljenje; prostata; prostate; sečila